Bent strain values affect the plastic deformation behaviours of twinned Ni NWs. (1st July 2019) - Wang, Lihua; Sun, Tao; Wei, Rujian; Guan, Pengfei; Liu, Pan; Chen, Minwei; Zhang, Ze; Han, Xiaodong
Abstract: Using homemade device, in situ atomic-scale bending experiments were conducted on twinned Ni nanowires. Many in situ atomic-scale observations revealed that the plastic behaviours of twinned Ni nanowires can be significantly affected by the magnitude of the bent strain. In the early stages of bending, their plastic deformation was controlled by dislocations. With increasing bending, fcc-bct phase transitions were observed. When the bent strain increased to a high level, grain boundary resulting from lattice distortion/collapse were detected. This study advances our understanding of the plasticity mechanisms of twinned Ni. Graphical abstract: Unlabelled Image